PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA PERCETAKAN DIGITAL KARUNIA PRINTING DI MAUMERE - Ameliansa Mahardika Batmaro; Antonius Phillipus K.Gheta; Pipiet Niken Aurelia (Universitas Nusa Nipa Maumere, 2026)
The background of this research is the fluctuation in the number of customers at Karunia Printing Digital Services in Maumere throughout 2025, as well as the existence of customer complaints regarding service quality and product quality. These issues indicate that customer loyalty has not yet been fully optimized. This research aimed to determine the influence of service quality and product quality on customer loyalty at Karunia Printing Digital Services in Maumere. This research used a quantitative approach using a survey method. The population of this research consisted of all customers of Karunia Printing Digital Services in Maumere. Data were collected through questionnaires, observations, interviews, and documentation. The data analysis techniques included descriptive analysis, validity testing, reliability testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) using SPSS software. The results of the research indicated that service quality had a positive and significant effect on customer loyalty. Product quality also had a positive and significant effect on customer loyalty. Furthermore, service quality and product quality simultaneously had a positive and significant effect on customer loyalty at Karunia Printing Digital Services in Maumere. These findings suggested that the better the service quality and product quality provided, the higher the level of customer loyalty. Keywords: Service Quality, Product Quality, Customer Loyalty